PROSES PEMBENTUKAN UNDANG-UNDANG DAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG: Analisis Undang-Undang Republik Indonesia Nomor 12 Tahun 2011 Tentang Pembentukan Peraturan Perundang-Undangan - Faqih, Muhammad (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2019)
This research aims to find out how establishment of legislation and PERPPU in perspective Law No. 12 of 2011 concerning Establisment of legislation. The research method used by the author is normative legal research trought a status approach and historical approach to analysis establisment of legislation used. Analysis Republic Indonesia Law No.12 of 2011. The results of the study showed that the process establishment of legislation the background is with an urgent situation that forces the process of its establishment to be cut short and some of its accelerated links to adjust state conditions in times of emergency. Whereas in the process of making law it is in accordance with Republic Indonesia Law No. 12 of 2011.